(untitled) (Biological Sciences - PJSIR, 2025)
Amidst global industrialization, rising release of harmful pollutants, like heavy metals, into water sources raises concerns for human health. In response, this study aimed to assess the efficacy of immobilized fungal biomass as a biosorbent for the removal of heavy metals like lead (Pb), copper (Cu) and nickel (Ni) from contaminated water. An economical biomaterial was developed by immobilization with fungal cells of Aspergillus oryzae onto Saccharum munja. The efficiency of this biosorbent was gauged through an atomic absorption spectrophotometer and by controlling the various process parameters such as pH, initial metal concentration, contact time, dosing rate and temperature. To comprehend the adsorption mechanism, the study employed kinetic modeling, adsorption isotherm analysis and thermodynamic investigations.